Specifying molecular determinants of the subcellular targeting of synaptic and extrasynaptic GABA A receptors - Arslan, Ayla (2006)
How GABA-A receptor subtypes segregate so precisely to different subcellular locations is not understood. In this study, I have expressed the recombinant g2 and d GABA-A receptor subunits in cultured hippocampal neurons to analyze the differential cell surface expression and sub-membrane segregation of synaptic and extrasynaptic GABA-A receptors. My data demonstrate that the synaptic targeting of g2-containing GABA-A receptors does not depend on the cytoplasmic TM3-TM4 domain of the g2 subunit. This result was actually surprising, until Alldred et al published their work last year (2005) showing that the synaptic localization of receptors with the g2 subunit requires the TM4 domain rather than the large TM3-TM4 cytoplasmic loop. The premise of our work, when we started, was that the loop region would be responsible. On the other hand, I showed here that the TM3-TM4 cytoplasmic domain of the d subunit is either a factor for the extra-synaptic clustering of the d containing GABAA receptors (this would be an active mechanism) or alternatively that this loop region may not contain any information at all on receptor targeting, and subunits with this domain may simply lack sufficient information to be placed in synapses (passive exclusion). I cannot currently distinguish between these two possibilities. Nevertheless, by comparing the d subunit TM3-TM4 loop amino acid sequences across the whole span of vertebrate evolution, I discovered that the loop was remarkably conserved. This would suggest that the loops tertiary structure and specific proteins that bind to it are important for some function(s)of d-containing receptors. A passive exclusion mechanism might have lead to a degeneration of the loop sequence.